2019
DOI: 10.1002/htj.21470
|View full text |Cite
|
Sign up to set email alerts
|

Stefan Blowing and Slip Effects on Unsteady Nanofluid Transport Past a Shrinking Sheet: Multiple Solutions

Abstract: The aim of a present article is to investigate the laminar unsteady two‐dimensional boundary layer flow of a nanofluid with Stefan blowing and slip effect. First, governing boundary layer equations are converted in the ordinary form of the differential equations (ODEs) from partial differential equations using appropriate coordinate transformations. The obtained ODEs are then solved by applying a shooting method with the Runge‐Kutta fourth order method by implementation of the Maple software. The influences of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(26 citation statements)
references
References 30 publications
0
26
0
Order By: Relevance
“…In order to perform a temporal analysis of the solutions' stability, introducing a new dimensionless time-dependent similarity transformation variable is required, as recommended by Merkin [32], Dero et al [33,34], and Lund et al [35][36][37]. Letting τ = ct (1−εt) yields the following new similarity transformation variables:…”
Section: Stability Analysismentioning
confidence: 99%
“…In order to perform a temporal analysis of the solutions' stability, introducing a new dimensionless time-dependent similarity transformation variable is required, as recommended by Merkin [32], Dero et al [33,34], and Lund et al [35][36][37]. Letting τ = ct (1−εt) yields the following new similarity transformation variables:…”
Section: Stability Analysismentioning
confidence: 99%
“…Nanofluid with the effect of Soret and Dufour was investigated and noticed a dual solution without performing the analysis of the stability of the solutions [34]. Dero et al [35] studied the unsteady flow of nanofluid on stretching/shrinking surface by considering various slip effects. Zaib et al [36] used a single-phase nanofluids model for micropolar fluid and found dual solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Crane 1 studied the stretching sheet flow problem for the first time and found analytical solutions to the Navier–Stokes equations. Then, many other researchers 2–5 worked on the stretching sheet with different physical features. However, Miklavcic and Wang 6 for the first time discussed flow on shrinking sheet while studying the liquid films flow on the unsteady stretching surface.…”
Section: Introductionmentioning
confidence: 99%